Global climate and soil cover – implications for land use in Russia - A. L. Ivanov; I. Yu. Savin; V. S. Stolbovoy; A. Yu. Dukhanin; D. N. Kozlov; I. M. Bamatov (Бюллетень Почвенного института им. В.В. Докучаева)
The necessity of a comprehensive description of greenhouse gas fluxes on different types of soils, the methodology for creating “carbon polygons” and “carbon farms” with the use of modern methods for assessing carbon fluxes in ecosystems, taking into account the specifics of the natural conditions of Russia and competitive advantages, are substantiated. Directions for developing national methods for calculating carbon fluxes are given, which should be subjected to verification by the interested parties of the Paris Agreement adopted by the Russian Federation. Such issues are considered as the role and potential of the Russian soil cover in the carbon balance of the planet, factors of reducing carbon stocks from the upper 1 meter depth layer of the soil, competitive edge in the EU and the Western world in the questions of natural and climatic changes, the use of remote sensing of the Earth from space in order to obtain regular, complete and reliable estimates of the absorption of greenhouse gases.